221k views
2 votes
Simplify (5x - 3y)³ - (5x + 3y)³​

User JBilbo
by
5.3k points

1 Answer

2 votes

Answer:

−6y((5x−3y)^2 +(5x−3y)(5x+3y)+(5x+3y)^2)

Explanation:

Use Difference of Cubes : a^3 - b^3 = (a-b)*(a^2+ab+b^2)

= (5x - 3y - (5x+3y))*((5x-3y)^2 + (5x-3y)*(5x+3y)+(5x+3y)^2)

Simplify brackets:

= (5x−3y−5x−3y)((5x−3y)​^2+(5x−3y)(5x+3y)+(5x+3y)^2)

Collect like temrs:

= ((5x−5x)+(−3y−3y))((5x−3y)^2​+(5x−3y)(5x+3y)+(5x+3y)^2)

Simplify:

= −6y((5x−3y)^2 +(5x−3y)(5x+3y)+(5x+3y)^2)

Simpliest form it can get!

Hope this helped :3

​​

​​

User Nebkat
by
5.4k points